ANALYSIS OF TEACHER NEEDS ON INTERACTIVE LEARNING MEDIA FOR DISTANCE LEARNING - Siti Nurkamilah; Rifaatul Muthmainnah (Akademika : Jurnal Teknologi Pendidikan, 2022)
This research aims to find out the need for teachers to interactive learning media for distance learning. This research is qualitative research using descriptive methods. The research subjects involved were biology teachers of High School and Madrasah Aliyah in Garut Regency. The results of this study show that students' initial understanding of biological materials is needed, then interactive learning media is needed in the distance learning process. The needs of content or materials in interactive learning media must be following the core competencies and basic competencies that exist in the school. The purpose of learning and material can be presented briefly and clearly. In addition, there needs to be an evaluation process at the end of interactive media in the form of multiple choices. For aspects of visual communication, bright colors are needed that do not mess with the look and provide comfort for students that are accompanied by animations, audio, images, appropriate typefaces, and accompanied by distinctive icons that can help students remember the material delivered. The media used in distance learning needs to be distinguished from the medium of learning directly so that students can easily understand the material presented in addition to the teacher can easily monitor the cognitive development of students. The perception of most teachers regarding the right interactive learning media used in the distance learning process is to use android and be easy to operate.